MAINTENANCE OF COLONIES OF CORNITERMES CUMULANS (BLATTODEA: TERMITIDAE) FOR PREFERENCE TESTING - Leitão-Lima, Patrícia da Silva; Lima, Eduardo do Valle (Seven Editora, 2025)
Termites are social insects, with differentiated castes for specific functions within the colony, and play an important ecological role, contributing to the recycling of nutrients and soil bioturbation. The species Cornitermes cumulans is known for its economic damage to forest plantations, especially eucalyptus seedlings. DOI: https://doi.org/10.56238/sevened2024.037-126